Interaction of tourism and creative industries in the Arctic territories: Areas of crossing - Zhelnina, Z. Yu.; Sizova, I. A.; Khoreva, L. V. (Zenodo, 2023)
The article presents the results of the study of tourism development in the Arctic through interaction tourism industry with organizations of creative industries. Using mixed research methods (quantitative while working with published research and qualitative while working with experts), first, allowed us to determine the areas and conditions of productive interaction between tourism and creative industries using the case of Murmansk region, and second, to develop a model of interaction (collaboration) of tourism and creative industries in the Arctic territories. As a result, problems of interaction among tourism and creative industries were identified in connection with different types of development of industries and recommendations were formed to overcome them. The research results confirm that the creative component as a completed service is in demand in the tourist market of Murmansk region due to the increase and diversification of the tourist flow, when tourists are ready to purchase services from the event sphere: participation in creative events, purchase of material creative products. The value and novelty of the results lies in the search for promising areas for the development of cooperation among tourism and creative industries in the Arctic tourism destination and the development of recommendations for overcoming existing barriers to this cooperation. As long as local peculiarities are taken into account, the findings could be applied to other Arctic territories. Originally published in https://stcc.rgutspubl.org/index.php/1/article/view/64